2022
DOI: 10.1101/2022.06.27.497788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping nanoscale forces and potentials in live cells with microsecond 3D single-particle tracking

Abstract: Abstract3D single-particle tracking has the potential to resolve the molecular level forces which dictate particle motion in biological systems. However, the information gleaned from 3D single-particle tracking often cannot resolve underlying nanoscale potentials due to limited spatiotemporal resolution. To this end, we introduce an active-feedback 3D tracking microscope that utilizes silver nanoparticles (AgNPs) as probes to study intricate biophysical events in live cells at the nanometer and microsecond sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
(63 reference statements)
2
3
0
Order By: Relevance
“…The long time scale trajectories traced out the shape of physical cellular structures such as the cytoskeleton and membrane protrusion, demonstrating that SVT is also a tool for studying intracellular structures that play a role in viral infection . Previous research using 3D-SPT revealed cylindrical patterned trajectories along cell surface microspikes, hemispherical diffusion on membrane blebs, and linear motions along a membrane protrusion. ,, In the highly sampled trajectories reported here, directed linear motion could be observed, consistent with viral trafficking along the microtubule network. Uniquely, the extremely long time scale of observation here, combined with high-speed 3D sampling, allowed the large scale geometry of the underlying network to be resolved.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The long time scale trajectories traced out the shape of physical cellular structures such as the cytoskeleton and membrane protrusion, demonstrating that SVT is also a tool for studying intracellular structures that play a role in viral infection . Previous research using 3D-SPT revealed cylindrical patterned trajectories along cell surface microspikes, hemispherical diffusion on membrane blebs, and linear motions along a membrane protrusion. ,, In the highly sampled trajectories reported here, directed linear motion could be observed, consistent with viral trafficking along the microtubule network. Uniquely, the extremely long time scale of observation here, combined with high-speed 3D sampling, allowed the large scale geometry of the underlying network to be resolved.…”
Section: Resultssupporting
confidence: 76%
“…For the particles described below, which have emission intensities in the 50 to 100 kHz range, the position could be updated every 10 to 20 μs, though with an intrinsic trade-off between temporal resolution and localization precision. If there were infinite amount of photons, the bin time could be further narrowed down and the temporal resolution would only be ultimately limited to the photon collection rate . The additional photons provided by the StayGold fluorescent proteins are critical to increasing both the observation window and the sampling rate in SVT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Previous research using 3D-SPT revealed cylindrical patterned trajectories along cell surface microspikes, hemispherical diffusion on membrane blebs, and linear motions along a membrane protrusion. 7, 29, 33 In the highly-sampled trajectories reported here, directed linear motion could be observed, consistent with viral trafficking along the microtubule network. Uniquely, the extremely long timescale of observation here, combined with high-speed 3D sampling, allowed the large scale geometry of the underlying network to be resolved.…”
Section: Resultssupporting
confidence: 75%
“…If there were infinite amount of photons, the bin time could be further narrowed down and the temporal resolution would only be ultimately limited to the photon collection rate. 29 The additional photons provided by the StayGold fluorescent proteins are critical to increasing both the observation window and sampling rate in SVT.…”
Section: High Spatiotemporal Svt Via 3d-smartmentioning
confidence: 99%